A Pharmacognostic and Preliminary Phytochemical Study of Epipremnum aureum (Linden & Andre) G. S. Bunting - Rita Himanshu Mehta; Ashok Bhagwat; Sharad Karmarkar; Chhaya Sawant (International Journal of Phytomedicine, 2013)
Epipremnum aureum (Linden & Andre) G.S. Bunting (Family Araceae) commonly known as Money plant is a vigorously growing liana. It is a common indoor plant generally used for ornamental purposes. It comprises numerous cultivars bearing leaves with white, yellow, or light green variegation. In the present study a pharmacognostic evaluation of the plant species was undertaken. In addition to the macroscopic and microscopic characterizations; evaluation of physicochemical characteristics; preliminary phytochemical parameters and HPTLC fingerprint analysis of the plant methanolic extracts has been carried out. The thin layer chromatographic analysis and the preliminary phytochemical studies of the hot and cold methanolic extracts of the leaves showed the presence of various phytochemical constituents such as alkaloids, tannins, flavonoids, triterpenoids, and saponins. These observations were further confirmed by HPTLC fingerprint analysis. The findings reported in this study can be said to be the first report on the pharmacognosy of E. aureum and will prove of immense use for the correct identification of the plant species which is of key importance in establishing pharmacopeial standards.